DEVELOPMENT OF ERASMUS + PROGRAM AT THE UNIVERSITY OF PRISTINA WITH TEMPORARY HEADQUARTERS IN KOSOVO MITROVICA (Heritage, 2020)
After closure of Tempus, European Union programme for reform and modernization of Higher Education at the end of 2013, European Commission promoted new integrated European Union programme Erasmus+ for a period from 2017-2021, which encompassed seven various programme for education, youth and sport of previous generation. Aside from seven implemented Tempus projects, University Pristina temporarily settled in Kosovska Mitrovica, continued with succesfull participation in Erasmus+ programme. Since 2015, university gained seven Erasmus+ Key Action 2: Capacity Building in Higher Education projects, which is the most significant action and represents the inheritance of Tempus programme. University also realised inter-institutional cooperation with big number of universities from European Union with whom he gained 10 International Credit Mobility projects aiming at promotion of students, academic and administrative staff mobility of this university.
Keywords: Key words: Erasmus , capacity building, mobility, education, youth, sport